Peran Pendidikan Moral-Etis dalam Mengembangkan Tugas Keterpanggilan Sebagai Pendeta - Claartje Pattinama (Peneliti.net, 2019)
This study aims to show the role of moral-ethical education for pastors in carrying out their calling duties as servants of the people, by referring to the pastor's competence to seek and save